2022
DOI: 10.1177/10732748221117900
|View full text |Cite
|
Sign up to set email alerts
|

Precancerous Lesion of the Cervix and Associated Factors Among Women of West Wollega, West Ethiopia, 2022

Abstract: Background Precancerous cervical lesion is an abnormality in the cells of the cervix that could eventually develop into cervical cancer. Cervical cancer is a public health problem that contributes to the death of women worldwide. In line with the high burden of the issue, the Ethiopian government had attempted to expand cervical cancer screening centers and recommendation of services to age-eligible as well as high-risk groups of women. Therefore, the study aimed to assess the prevalence of precancerous lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
3
0
1
Order By: Relevance
“…The odds of developing pre-cancerous cervical lesions among women with a history of sexually transmitted infections were higher than among women who had no history of STIs. This finding was consistent with the studies conducted in Southern Ethiopia, Addis Ababa, three referral Hospitals in Amhara region, North Shoa, and Wollega which revealed that women who had a history of sexually transmitted infection were at higher risk of developing precancerous cervical lesions infection [ 12 , 35 , 39 – 41 ]. This could be due to the sexually transmitted nature of HPV infection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The odds of developing pre-cancerous cervical lesions among women with a history of sexually transmitted infections were higher than among women who had no history of STIs. This finding was consistent with the studies conducted in Southern Ethiopia, Addis Ababa, three referral Hospitals in Amhara region, North Shoa, and Wollega which revealed that women who had a history of sexually transmitted infection were at higher risk of developing precancerous cervical lesions infection [ 12 , 35 , 39 – 41 ]. This could be due to the sexually transmitted nature of HPV infection.…”
Section: Discussionsupporting
confidence: 91%
“…This could be because women who have had 2 or more lifetime sexual partners are more likely to develop precancerous cervical lesions, as the number of sexual partners increases; they are more likely to contract the HPV infection, which is the cause of cervical cancer and invasive cervical cancer. However, other studies done in selected hospitals of West Wollega showed that having a History of multiple sexual partners was not associated with the risk of precancerous cervical lesion development [ 39 ]. The possible reason for the difference might be the difference in the awareness level of sexual partners and/or the awareness level of commercial sex workers on the transmission and prevention methods of STI.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital studies have also reported a very high prevalence of precancerous cervical lesions. This is the case of a study carried out on 339 women in Ethiopia, which reported a prevalence of pre-cancerous lesions of 27.4% [27]. Another study conducted in Ethiopia in 2021 among 293 women in hospitals reported a prevalence of 15.7% [23].…”
Section: Discussionmentioning
confidence: 95%
“…OR: odds ratio, IC: intervalo de confianza, Inf: inferior, Sup: superior, p: prueba chi-cuadrado dIscusIón La neoplasia cervical representa un problema de salud pública pendiente para las naciones de ingresos altos y bajos. A nivel global la tasa de mortalidad alta por CCU podría mermar mediante un abordaje integral, que incluye la prevención, identificación de los factores de riesgo, temprana detección y eficaz tratamiento (15,16) . La identificación de los factores asociados para lesiones precancerosas de cuello uterino es relevante para que los encargados de formular políticas desarrollen estrategias preventivas.…”
Section: Resultsunclassified